Effect of Cryopreserved Placenta Tissue Implantation on Myocardium Morphology Under Experimental Atherosclerosis - Kondakov, I. I.; Yurchenko, T. N.; Sharlay, T. M. (Problems of Cryobiology and Cryomedicine, 2011)
Administration of allogeneic cryopreserved placenta tissue (ACP) on the background of termination of atherogenic diet has been shown to accelerate the atherosclerosis regression in the great branches of coronary arteries and resulted in neoangiogenesis of myocardium intramural vessels, which was confirmed by the statistically significant rise in their number per unit of cardiac muscle area.